Perception of dentists, dental students, and patients on dentogingival aesthetics - Migueli DURIGON; Bruno Pinto ALESSI; Matheus NEVES; Micheline Sandini TRENTIN (Revista de Odontologia da UNESP)
Abstract Introduction Patients’ demand for dentogingival aesthetics has increased significantly in recent years, and this is a complex concept due to numerous factors involved in obtaining patient/professional satisfaction. Some dentogingival features may alter smile harmony, such as excessive gingival display. Objective To evaluate whether the presence of gingival display has a negative influence on the perception of dentogingival aesthetics. Material and method 180 individuals (60 dentists, 60 dental students, and 60 patients) evaluated images of volunteer smiles. These images were digitally altered by the Adobe Photoshop™ software, creating different situations of gingival display (4 mm, 2 mm, 0 mm, -2 mm, -4 mm), and graded by the evaluators with the following scores: (01) very pleasant smile, (02) pleasant smile, and 03) unpleasant smile. The scores assigned were analyzed using ANOVA (α=0.05). Result Gingival displays between 0 and 2 mm were considered aesthetically pleasing. Changes of -4 and +4 mm were defined as the most disharmonious smiles. The 0-mm female smile was considered the most harmonious for dentists (1.51) and dental students (1.77), by Student's t test (p<0.05). In the opinion of patients, the smile of +2 mm was considered the most aesthetic. In the image evaluations of men, the 0-mm smile was considered the most aesthetic (p <0.05) for dentists (1.85) and dental students (1.62). The patients considered +2 mm of gingival display the most harmonious smile. Conclusion The aesthetic perception of dental students and dentists was different when compared to the group of patients.